Knowledge and attitudes regarding non‐invasive prenatal testing among women in Saudi Arabia. (27th June 2021) - Bawazeer, Shahad; AlSayed, Moeenaldeen; Kurdi, Wesam; Balobaid, Ameera
Abstract: Objectives: To explore women's knowledge and attitudes regarding NIPT, its implications, the factors affecting their decision to undergo the test and actions taken following a positive result. Methods: In this descriptive study, women who were offered NIPT through the foetal maternal clinic, were asked to complete an anonymous questionnaire about NIPT. The questionnaire consisted of 29 statements and covered four areas: demographics, knowledge, attitudes and decision‐making. Results: A total of 150 women who were offered NIPT participated in this study. The results showed that generally women had poor knowledge of critical aspects of NIPT. This included the conditions tested for, the implications of the test and its limitations. Over 90% of women were in favour of NIPT and it being offered to all women of advanced maternal age while 66% of the tested women agreed to having confirmatory invasive testing in the case of a positive result. Conclusion: This study shows that the acceptance rate for NIPT is high despite incomplete understanding of the benefits and limitations of the test. The study findings support the need for education regarding this test through dedicated genetic counselling sessions in order to ensure that an informed decision can be made. Key Points: What is already known about this topic? NIPT is an emerging screening tool that is being introduced into prenatal care. Pre‐test and post‐test genetic counselling alongside NIPT is important. What does this study add? To our knowledge, this is the first study to explore the attitudes and knowledge of women in Saudi Arabia about NIPT. This study begins to address the gap in our knowledge and contributes to practicing evidence‐based genetic counselling.